2023
DOI: 10.3390/separations10080421
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Antioxidant Activity and Cholinesterase Inhibition Potential of Essential Oil and Extracts of Teucrium montanum from Bosnia and Herzegovina

Abstract: Bioactive compounds from plants play an important role in slowing many neurodegenerative diseases, such as Alzheimer’s disease, by inhibiting cholinesterase enzymes. Studies have shown that oxidative stress is associated with the development of Alzheimer’s disease. In traditional medicine of Bosnia and Herzegovina, Teucrium montanum is used to treat numerous diseases. The chemical composition and biological activity of the essential oil (EO) and aqueous (AE) and methanol extract (ME) of this plant were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
2
9
3
Order By: Relevance
“…The EOs were isolated from dry plant materials by hydrodistillation (Clevenger apparatus, 3 h) following the procedure reported by Bektašević et al [ 32 ]. The separated EOs were dried over anhydrous Na 2 SO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The EOs were isolated from dry plant materials by hydrodistillation (Clevenger apparatus, 3 h) following the procedure reported by Bektašević et al [ 32 ]. The separated EOs were dried over anhydrous Na 2 SO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…To this end, mostly phenolic acids and flavonoids were quantified in T. montanum extracts [8][9][10]. However, it can be seen that T. montanum extract, as a generally understudied plant species in terms of bioactive profile, is shown to be a notable source of PGs, in comparison to its commercial plant sources (Table 2).…”
Section: Determination Of Hc and Phenolic Compounds In Extractmentioning
confidence: 99%
“…Supported by significant scientific evidence in terms of disease prevention, anti-aging, and immune system boosting effects, polyphenols have emerged as one of the most attractive antioxidants today [5][6][7]. Among the identified hydroxybenzoic and hydroxycinnamic acids, flavones, and flavone glycosides [8][9][10], phenylethanoid glycosides (PGs) represent the most understudied phenolic group found in T. montanum extracts. The latest studies show that PGs are promising neuroprotective [11], anticancer [12], anti-obesity [13], anti-inflammatory [14], and antibacterial [15] agents.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 72 ethnobotanical studies conducted so far on Teucrium L., 20 species have been confirmed for their medicinal purposes in various treatments, mainly for abdominal pain and gastrointestinal complaints reported in a total of 56 studies [5,6], followed by treating spasms, treating rheumatism and as blood purification therapy [7], treating hemorrhoids [8], treating respiratory diseases [9], strengthening the immune system [10], etc. The limited studies conducted so far report antimicrobial [11], anti-inflammatory [12], antiulcerogenic [13], radical scavenging [14], and lipid-protective activities [15] of Teucrium species. These effects are related to the presence of secondary metabolites, such as BC, e.g., phenolic compounds, whose long-term consumption has been shown to play an important role in suppressing oxidative cell damage and the prevalence of various chronic diseases [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Among the polyphenols identified so far in Teucrium L., flavonoids represent the most extensive subgroup, e.g., luteolin and its glycosides, apigenin and its glycosides, vicenin-2, isoquercetin, rutin, (epi)catechin, etc. [15,20,21]. Some studies also reported the presence of hydroxybenzoic and hydroxycinnamic acids, including gallic acid, protocatechuic acid, vanillic acid, caffeic acid, chlorogenic acid, p-coumaric acid, etc.…”
Section: Introductionmentioning
confidence: 99%